2013
DOI: 10.1016/s1470-2045(13)70479-0
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel and dasatinib or placebo in men with metastatic castration-resistant prostate cancer (READY): a randomised, double-blind phase 3 trial

Abstract: Summary Background Src kinase-mediated interactions between prostate cancer cells and osteoclasts might promote bone metastasis. Dasatinib inhibits tyrosine kinases, including Src kinases. Data suggests that dasatinib kinase inhibition leads to antitumour activity, affects osteoclasts, and has synergy with docetaxel, a first-line chemotherapy for metastatic castration-resistant prostate cancer. We assessed whether dasatinib plus docetaxel in chemotherapy-naive men with metastatic castration-resistant prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(136 citation statements)
references
References 35 publications
3
130
0
3
Order By: Relevance
“…Thus, dasatinib, a potent oral inhibitor of SRC family and other kinases (45), has been used in the treatment of metastatic prostate cancer. Unfortunately, the READY trial, a randomized, double-blind phase 3 trial, did not demonstrate a survival benefit upon the addition of dasatinib to docetaxel in chemotherapy-naive CRPC patients (46). One concern is that the heterogeneity of CRPC may require the preselection of specific categories of patients likely to benefit from SRC family kinase inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, dasatinib, a potent oral inhibitor of SRC family and other kinases (45), has been used in the treatment of metastatic prostate cancer. Unfortunately, the READY trial, a randomized, double-blind phase 3 trial, did not demonstrate a survival benefit upon the addition of dasatinib to docetaxel in chemotherapy-naive CRPC patients (46). One concern is that the heterogeneity of CRPC may require the preselection of specific categories of patients likely to benefit from SRC family kinase inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…This was particularly true for studies evaluating combinations of chemotherapy and targeted agents where the corresponding preclinical studies evaluated targeted agents used alone. For some trials there was simply a claim of sufficient preclinical evidence to conduct such trials (6)(7)(8). Appropriate preclinical studies may have been conducted, but were not reported.…”
Section: Preclinical Cancer Research To Support Drug Developmentmentioning
confidence: 99%
“…A maximum-tolerated dose of 80 mg/kg/d for dasatinib (6 d of continuous administration) was determined in our pilot study, and 50% of the maximum tolerated dose was used in this study. After the baseline imaging (day 0), animals in the treatment groups were administered dasatinib (40 mg/kg/d) (in 1:1 propylene glycol/water) via gavage for 6 d (days [1][2][3][4][5][6]. Animals in the control groups were administered 1:1 propylene glycol/water (vehicle control) using the same protocol.…”
Section: Cell Culture and Animal Modelmentioning
confidence: 99%